2020
DOI: 10.1186/s12929-019-0604-z
|View full text |Cite
|
Sign up to set email alerts
|

7-oxo-DHEA enhances impaired M. tuberculosis-specific T cell responses during HIV-TB coinfection

Abstract: Background: Mycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis (TB), affecting approximately one third of the world's population. Development of an adequate immune response will determine disease progression or progress to chronic infection. Risk of developing TB among human immunodeficiency virus (HIV)-coinfected patients (HIV-TB) is 20-30 times higher than those without HIV infection, and a synergistic interplay between these two pathogens accelerates the decline in immunological functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Formerly, we described that 7-OD modulated CD4 + T cells Mtb-speci c responses, biasing phenotype and cytokine balance towards a more favorable pro le for mycobacteria control [22]. Therefore, the absolute levels (Supplementary Fig.…”
Section: -Od Improved the Killing Of Mtb By Human Macrophagesmentioning
confidence: 96%
See 1 more Smart Citation
“…Formerly, we described that 7-OD modulated CD4 + T cells Mtb-speci c responses, biasing phenotype and cytokine balance towards a more favorable pro le for mycobacteria control [22]. Therefore, the absolute levels (Supplementary Fig.…”
Section: -Od Improved the Killing Of Mtb By Human Macrophagesmentioning
confidence: 96%
“…Previous research has shown that endogenous levels of 7-OD positively correlated with clinical parameters associated with a better outcome and the restriction of TB to the lungs in HIV-TB coinfected patients. Moreover, 7-OD enhanced Th1 responses of in vitro Mtb-stimulated peripheral blood mononuclear cells from HIV-TB coinfected patients by increasing proliferation, the production of IFN-γ and TNF-α, and the frequency of the CD4 + T-bet + subset [22]. Inasmuch as 7-OD modi ed the cytokine balance and the phenotype of CD4 + T cells towards a more favorable pro le for mycobacteria control in an in vitro model, the aim of this work was to study its role as a potential adjunctive treatment for TB.…”
Section: Introductionmentioning
confidence: 95%
“…with HIV is 20-30-fold higher than for those without HIV and the synergistic interplay of the two pathogens accelerates the decrease in immunological function (7). Pulmonary TB is the most common form of active TB in patients with HIV (8).…”
Section: Changes In the Balance Of Th17/treg Cells And Oxidative Stre...mentioning
confidence: 99%
“…In 2019, 208,000 of ~1.4 million TB-related deaths were among HIV-positive people ( 6 ). The risk of developing TB for patients with HIV is 20-30-fold higher than for those without HIV and the synergistic interplay of the two pathogens accelerates the decrease in immunological function ( 7 ). Pulmonary TB is the most common form of active TB in patients with HIV ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was even recommended as a drug preventing Raynaud’s syndrome attacks (Kazihnitková et al ., 2007). 7‐Oxo‐DHEA may serve as natural antiglucocorticoid (Muller et al ., 2006), and it may be involved in the development of an effective immune response (Arsenou et al ., 2003; Vecchione et al ., 2020). It has been suggested that 7‐oxo‐DHEA as an antagonist of γ‐aminobutyric acid subtype A receptor (GABA A ) exerts a beneficial effect for memory retention in mice.…”
Section: Introductionmentioning
confidence: 99%